Relational analysis of the graduation profile of the unified general baccalaureate and the academic offer of the Pedagogy in Experimental Sciences and Computer Science degree program - Cabascango-Trávez, Gladys (2022)
In the course of high school, Ecuadorian students take the exam Ser bachiller, a component that allows access to higher education, that is why this research focused on knowing the factors that affect the relationship of the graduation profile of the students of the Unified General Baccalaureate for the entrance to the Pedagogy Career in Experimental Sciences of Computer Science of the Faculty of Philosophy, Letters and Educational Sciences at the Central University of Ecuador. Non-experimental research was carried out, with a field approach, at a descriptive level, using quantitative methodology, data was collected; in addition, a test was conducted, which worked with the students entering the career as essential informants and data was processed using SPSS 23 statistical software. Among the main findings, it was evidenced that the students graduated under the BGU program of study evidence certain deficiencies before the demands of the entrance profile required by the Central University of Ecuador, also that the skills and abilities acquired by the BGU students are elementary, and the expectations that the students reach the level of excellent achievement is scarce; decreasing the possibilities of entering higher education.